2015
DOI: 10.1007/s00125-015-3499-6
|View full text |Cite
|
Sign up to set email alerts
|

Leisure-time physical activity and development and progression of diabetic nephropathy in type 1 diabetes: the FinnDiane Study

Abstract: Aims/hypothesis The aim of this study was to assess how physical activity predicts the development and progression of diabetic nephropathy in patients with type 1 diabetes. Methods This prospective study (follow-up time 6.4 ± 3.1 years) included 1,390 patients (48.5% men, mean age 37.0±12.4 years, duration of diabetes 20.4±12.3 years) participating in the nationwide multicentre Finnish Diabetic Nephropathy (FinnDiane) Study. Leisure-time physical activity (LTPA) was assessed using a validated self-report quest… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
35
0
1

Year Published

2015
2015
2022
2022

Publication Types

Select...
4
4
1

Relationship

1
8

Authors

Journals

citations
Cited by 53 publications
(37 citation statements)
references
References 26 publications
1
35
0
1
Order By: Relevance
“…115 In addition, in patients with type 1 diabetes, higher levels of leisure-time physical activity were associated with less progression to renal failure (on the basis of urinary albumin excretion rate) and less incidence of microalbuminuria over 6 years of follow up. 116…”
Section: Low Birth Weightmentioning
confidence: 99%
“…115 In addition, in patients with type 1 diabetes, higher levels of leisure-time physical activity were associated with less progression to renal failure (on the basis of urinary albumin excretion rate) and less incidence of microalbuminuria over 6 years of follow up. 116…”
Section: Low Birth Weightmentioning
confidence: 99%
“…In a separate analysis, exercise intensity also had a borderline effect on recurrencefree time in patients with a major CVD event at baseline. We previously showed that the intensity of exercise, rather than the total amount of LTPA, predicts the progression and development of diabetic nephropathy in type 1 diabetes [7]. We have also shown that lower intensity is associated with prevalent CVD in a cross-sectional setting [2].…”
Section: Discussionmentioning
confidence: 93%
“…We recently reported that the intensity of physical activity might have an impact on the incidence and progression of diabetic nephropathy [7]. In addition, an increasing body of evidence suggests that the complications of type 1 diabetes, namely CVD and diabetic nephropathy, share risk factors and develop in parallel [8].…”
Section: Iqrmentioning
confidence: 99%
“…Possible mechanisms that link PA to the prevention of the progression and remission of microvascular complications in patients with type 2 diabetes reportedly include the following: reduction of blood pressure, improvements in lipid profile, glycemic control, insulin sensitivity, and endothelial function [3438]. However, our results show that the association is robust after adjusting for sBP, dBP, BMI, and HbA1c level as time-varying variables, suggesting that PA could lower the risk of developing DR via pathways other than blood pressure, BMI, and glycemic control.…”
Section: Discussionmentioning
confidence: 99%